Intrauterine insemination versus intracervical insemination in donor sperm treatment - Kop, Petronella AL (Cochrane Database Syst Rev, 2018)
BACKGROUND: The first‐line treatment in donor sperm treatment consists of inseminations that can be done by intrauterine insemination (IUI) or by intracervical insemination (ICI). OBJECTIVES: To compare the effectiveness and safety of intrauterine insemination (IUI) and intracervical insemination (ICI) in women who start donor sperm treatment. SEARCH METHODS: We searched the Cochrane Gynaecology and Fertility Group Trials Register, CENTRAL, MEDLINE, Embase, PsycINFO, CINAHL in October 2016, checked references of relevant studies, and contacted study authors and experts in the field to identify additional studies. We searched PubMed, Google Scholar, the Grey literature, and five trials registers on 15 December 2017. SELECTION CRITERIA: We included randomised controlled trials (RCTs) reporting on IUI versus ICI in natural cycles or with ovarian stimulation, and RCTs comparing different cointerventions in IUI and ICI. We included cross‐over studies if pre‐cross‐over data were available. DATA COLLECTION AND ANALYSIS: We used standard methodological procedures recommended by Cochrane. We collected data on primary outcomes of live birth and multiple pregnancy rates, and on secondary outcomes of clinical pregnancy, miscarriage, and cancellation rates. MAIN RESULTS: We included six RCTs (708 women analysed) on ICI and IUI in donor sperm treatment. Two studies compared IUI and ICI in natural cycles, two studies compared IUI and ICI in gonadotrophin‐stimulated cycles, and two studies compared timing of IUI and ICI. There was very low‐quality evidence; the main limitations were risk of bias due to poor reporting of study methods, and serious imprecision. IUI versus ICI in natural cycles There was insufficient evidence to determine whether there was any clear difference in live birth rate between IUI and ICI in natural cycles (odds ratio (OR) 3.24, 95% confidence interval (CI) 0.12 to 87.13; 1 RCT, 26 women; very low‐quality evidence). There was only one live birth in this study (in the IUI group). IUI resulted in higher clinical pregnancy rates (OR 6.18, 95% CI 1.91 to 20.03; 2 RCTs, 76 women; I² = 48%; very low‐quality evidence). No multiple pregnancies or miscarriages occurred in this study. IUI versus ICI in gonadotrophin‐stimulated cycles There was insufficient evidence to determine whether there was any clear difference in live birth rate between IUI and ICI in gonadotrophin‐stimulated cycles (OR 2.55, 95% CI 0.72 to 8.96; 1 RCT, 43 women; very low‐quality evidence). This suggested that if the chance of a live birth following ICI in gonadotrophin‐stimulated cycles was assumed to be 30%, the chance following IUI in gonadotrophin‐stimulated cycles would be between 24% and 80%. IUI may result in higher clinical pregnancy rates than ICI (OR 2.83, 95% CI 1.38 to 5.78; 2 RCTs, 131 women; I² = 0%; very low‐quality evidence). IUI may be associated with higher multiple pregnancy rates than ICI (OR 2.77, 95% CI 1.00 to 7.69; 2 RCTs, 131 women; I² = 0%; very low‐quality evidence). This suggested that if the risk of multiple pregnancy following ICI in gonadotrophin‐stimulated cycles was assumed to be 10%, the risk following IUI would be between 10% and 46%. We found insufficient evidence to determine whether there was any clear difference between the groups in miscarriage rates in gonadotrophin‐stimulated cycles (OR 1.97, 95% CI 0.43 to 9.04; 2 RCTs, overall 67 pregnancies; I² = 50%; very low‐quality evidence). Timing of IUI and ICI We found no studies that reported on live birth rates. We found a higher clinical pregnancy rate when IUI was timed one day after a rise in blood levels of luteinising hormone (LH) compared to IUI two days after a rise in blood levels of LH (OR 2.00, 95% CI 1.14 to 3.53; 1 RCT, 351 women; low‐quality evidence). We found insufficient evidence to determine whether there was any clear difference in clinical pregnancy rates between ICI timed after a rise in urinary levels of LH versus a rise in basal temperature plus cervical mucus scores (OR 1.31, 95% CI 0.42 to 4.11; 1 RCT, 56 women; very low‐quality evidence). Neither of these studies reported multiple pregnancy or miscarriage rates as outcomes. AUTHORS' CONCLUSIONS: There was insufficient evidence to determine whether there was a clear difference in live birth rates between IUI and ICI in natural or gonadotrophin‐stimulated cycles in women who started with donor sperm treatment. There was insufficient evidence available for the effect of timing of IUI or ICI on live birth rates. Very low‐quality data suggested that in gonadotrophin‐stimulated cycles, IUI may be associated with a higher clinical pregnancy rate than ICI, but also with a higher risk of multiple pregnancy rate. We concluded that the current evidence was too limited to choose between IUI or ICI, in natural cycles or with ovarian stimulation, in donor sperm treatment.